Physical–biological interactions underlying the connectivity patterns of coral‐dependent fishes around the Arabian Peninsula. (4th February 2022) - Torquato, Felipe; Møller, Peter R.
Abstract: Aim: Distribution patterns of lineages alone do not explain the processes underlying phylogenetic differentiation in fishes observed around the Arabian Peninsula, whose hypotheses traditionally rely on (i) Pleistocene vicariance events, (ii) successive bottlenecks, (iii) recent founder effects (iv) and large spatial gradients in physical conditions. In this study, we test the hypothesis that phylogeographical patterns of coral‐dependent fish species inhabiting the peninsula may be driven by a combination of ocean circulation, larval behaviour and seascape features. Location: Arabian Peninsula. Taxa: Coral reef fish. Methods: A biophysical modelling system that relies on stochastic Lagrangian framework and Individual‐Based Model was used to simulate larval dispersal through three putative barriers, by tracking three‐dimensional movements of virtual particles in ocean circulation scenarios. We explored the range of dispersal capabilities across reef fish species by creating 72 hypothetical strategies, each representing a unique combination of five biological traits, namely pelagic larval duration, spawning periodicity, mortality rate, reproductive output and vertical migration. Results: The strength of the barriers was highly variable as a function of all biological traits (except reproductive output) and indicated high asymmetry of connectivity, and hence gene flow, between adjacent areas. In addition, direction and distance travelled by the virtual larvae varied according to both the geographical position of releasing site and biannual monsoonal winds. On average, larvae released during the summer exhibited a higher potential for dispersal than larvae released during the winter. Main conclusions: Our biophysical models showed that in the Arabian Peninsula, the combination of hydrodynamic, seascape features and larval traits likely affects the distribution of genetic lineages due to the interruption, reduction or asymmetry of larval movements through the putative barriers.